Varicella-zoster virus vasculopathy: a rare complication of Ramsay Hunt Syndrome: a literature review - Wu, Di; Song, Mian (Frontiers in Neurology, 2025)
BackgroundRamsay Hunt Syndrome TypeII (RHSII), also known as herpes zoster oticus, is an example of reactivation of the varicella-zoster virus (VZV) at the geniculate ganglion. Although rare, reports of VZV vasculopathy secondary to RHSII have been documented. The aim of this review was to analyze clinical and neuroimaging findings, laboratory findings, treatment and outcome of these patients.MethodsWe report a literature review that includes all case reports identified via PubMed on RHSII complicated by VZV Vasculopathy. All epidemiological, clinical, imaging, virologic, treatment and outcome data collected are described.ResultsWe analyzed a total of RHSII complicated by VZV vasculopathy 9 cases (median age 54.0 ± 16.5 years, range 24–75), and 22.2% (2/9) were immunocompromised. Apart from RHSII-related symptoms, the most common symptom is cranial nerve injury (77.8%, 7/9). Abnormal brain imaging in 88.9% (8/9), including 8 cases of ischemic stroke and one of which was accompanied by hemorrhagic stroke. Vascular studies revealing abnormalities in 66.7% (6/9) cases. Cerebrospinal fluid (CSF) analysis revealed 5 (55.6%, 5/9) cases were positive for VZV IgG, and 5 (55.6%, 5/9) cases tested positive for VZV DNA. All 9 patients received acyclovir treatment, with 77.8% (7/9) combination with corticosteroids. A favorable outcome was observed in 88.9% (8/9) of the patients. We analyzed a total of 9 cases of RHS II complicated by VZV vasculopathy. The median age was 54.0 ± 16.5 years (range 24–75), with 22.2% (2/9) being immunocompromised. In addition to RHS II-related symptoms, cranial nerve injury was the most common symptom, occurring in 77.8% (7/9) of cases. Abnormal brain imaging was observed in 88.9% (8/9) of patients, including 8 cases of ischemic stroke, one of which was accompanied by hemorrhagic stroke. Vascular studies revealed abnormalities in 66.7% (6/9) of cases. Cerebrospinal fluid (CSF) analysis showed that 5 patients (55.6%) were positive for VZV IgG, and 5 patients (55.6%) tested positive for VZV DNA. All 9 patients received acyclovir treatment, with 77.8% (7/9) also receiving corticosteroids. A favorable outcome was observed in 88.9% (8/9) of the patients.ConclusionVZV vasculopathy, as a rare complication of RHSII, can occur in both immunocompetent and immunosuppressed patients. Ophthalmoplegia is its primary clinical manifestation. Detection of VZV IgG antibodies and VZV DNA in the CSF has equal sensitivity. Antiviral combined with steroid therapy represents the optimal treatment approach.